Composite films of poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate incorporated with carbon nanotube sheet for improved power factor in thermoelectric conversion. (December 2020) - Kim, Ju Hyeon; Kang, Tae June
Highlights: PEDOT:PSS based composites were fabricated by incorporating a CNT sheet. Morphology of the composites was analyzed using AFM and SEM. Seebeck coefficient and electrical conductivity of the composites were measured. The power factors of the specimens were evaluated. The power factor was significantly increased from 3.53 nW/m∙K 2 to 30.54 μW/m∙K 2 . Abstract: The flexible nature of organic thermoelectrics greatly extends the scope of applications of thermoelectric energy conversion. However, their relatively low electrical conductivity and Seebeck coefficient compared to those inorganic thermoelectrics limit the output current of thermoelectrics to having a low power factor. In this work, we fabricated poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) composites by incorporating a carbon nanotube (CNT) sheet as a high-performance thermoelectric filler. The electrical conductivity and Seebeck coefficient of pure PEDOT:PSS and the composite films were measured and the corresponding power factors of the films were compared. Compared to the electrical conductivity of 0.74 S/cm and the Seebeck coefficient of 7.0 μV/K noted for PEDOT:PSS films, both thermoelectric properties were remarkably enhanced for the PEDOT:PSS/CNT sheet composites, at 170 S/cm and 42.5 μV/K, respectively. In terms of the power factor, the increase was almost 4 times higher, from 3.53 nW/m∙K 2 to 30.54 μW/m∙K 2, demonstrating a greatly improved ability to generate electrical energy for a thermoelectric device.